2020
DOI: 10.1111/jgh.15288
|View full text |Cite
|
Sign up to set email alerts
|

Does anti‐tumor necrosis factor alpha prevent the recurrence of Crohn's disease? Systematic review and meta‐analysis

Abstract: Background and Aim: Anti-tumor necrosis factor (TNF) α agents are now well known to function as effective treatments for Crohn's disease (CD). Several meta-analyses have revealed the efficacy of anti-TNF therapy for preventing recurrence after surgery; however, the efficacies reported in some prospective studies differed according to the outcomes. Moreover, adverse events (AEs) were not well evaluated. We conducted this systematic review and meta-analysis to evaluate both the efficacy of anti-TNF therapy after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We performed a systematic review and meta-analysis of a total of 570 patients, including 254 in an intervention group and 316 in a control group [ 225 ]. The results of eight randomized control studies performed to determine efficacy of anti-TNF-α agents administered after surgery for the prevention of endoscopic recurrence [relative risk (RR) 0.34, 95% CI 0.22–0.53] showed no increase in AEs (RR 1.75, 95% CI 0.81–3.79).…”
Section: Anti-tnf-α Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a systematic review and meta-analysis of a total of 570 patients, including 254 in an intervention group and 316 in a control group [ 225 ]. The results of eight randomized control studies performed to determine efficacy of anti-TNF-α agents administered after surgery for the prevention of endoscopic recurrence [relative risk (RR) 0.34, 95% CI 0.22–0.53] showed no increase in AEs (RR 1.75, 95% CI 0.81–3.79).…”
Section: Anti-tnf-α Agentsmentioning
confidence: 99%
“…The results of eight randomized control studies performed to determine efficacy of anti-TNF-α agents administered after surgery for the prevention of endoscopic recurrence [relative risk (RR) 0.34, 95% CI 0.22–0.53] showed no increase in AEs (RR 1.75, 95% CI 0.81–3.79). However, clinical recurrence was not prevented (RR 0.60, 95% CI 0.36–1.02) [ 225 ].…”
Section: Anti-tnf-α Agentsmentioning
confidence: 99%
“…Although the body of evidence is relatively small, the prophylactic use of anti-TNF has been reported to prevent clinical and endoscopic recurrence in the first 2 years, yet the effect on long-term outcomes remains elusive. 63 The immunological mechanisms underlying recurrence after macroscopic resetting are still being investigated but may involve upregulation of several genes (TNF-α, IFNγ, IL23A, and IL17A) and pathways (mitochondrial dysfunction and JAK-STAT). 64 …”
Section: Early Intervention and Impact On Prognosismentioning
confidence: 99%
“…A meta‐analysis showed that anti‐TNF‐α agents prevented endoscopic recurrence (RR: 0.34) but not clinical recurrence (RR: 0.60, not significant [n.s.]). Patients receiving anti‐TNFα therapy experienced more adverse effects than those who were not (RR: 1.75) 19 . Curcumin, as an adjuvant treatment for mesalamine, was proven to be effective in inducing clinical remission (odds ratio [OR]: 5.2), endoscopic remission (OR: 5.7), and endoscopic improvement (OR: 17.1), and was shown to be safe in UC 20 …”
Section: Ibdmentioning
confidence: 99%
“…Patients receiving anti-TNFα therapy experienced more adverse effects than those who were not (RR: 1.75). 19 Curcumin, as an adjuvant treatment for mesalamine, was proven to be effective in inducing clinical remission (odds ratio [OR]: 5.2), endoscopic remission (OR: 5.7), and endoscopic improvement (OR:…”
Section: Periodontitismentioning
confidence: 99%